Conversion of amyloid fibrils of cytochrome c to mature nanorods through a honeycomb morphology - Haldar, Shubhasis (Langmuir : the ACS journal of surfaces and colloids, 2015)
Amyloid species with various morphologies have been found for different proteins and disease systems. In this article, we aim to ask if these morphologies are unique to a particular protein or if they convert from one to another. Using a heme protein containing iron as the transition-metal activator of aggregation and a negatively charged surfactant, partial unfolding of the protein and its aggregation have been induced. In the pathway of aggregation, we have observed the formation of several morphological structures of a single protein, which were visualized directly using atomic force microscopy (AFM). These structures have been found to appear and disappear with time, and their formation could be monitored under normal buffer conditions and at room temperature without requiring any sophisticated chemical or biological methodologies. In addition, we have observed the formation of honeycomb-shaped morphology, which may serve as an intermediate. These amyloid-based nanostructures may have the potential to be explored in therapeutics delivery and other biomedical applications